Cannabis Use and Individual Health Measures - Weiwei Chen; Michael T. French (Medical Care Research and Review, 2026)
Despite growing acceptance of cannabis, considerable knowledge gaps persist regarding its effects on overall health status and quality of life. This study examines the impact of cannabis use on individuals’ overall, physical, and mental health status. To address potential endogeneity in cannabis use, we employ an instrumental variable (IV) approach using individual-level data. Three sets of IVs—state-level cannabis laws, cannabis prices, and average cannabis use within matched gender-age groups—are used to estimate two-stage least-squares models. While the results vary across health measures and IVs, the findings based on the strongest IV—group average cannabis use—suggest that more days of cannabis use are associated with fewer days in good mental health among users aged 21 to 64, particularly males. For adults aged 65 and older, the effects are mixed.